Teacher training and Pedagogical Political Project: Advances and challenges - Santos, Vulmara Galho dos; Teixeira , Igor Galho (Seven Editora, 2024)
This work addresses Rural Education and its nuances related to the Political Pedagogical Project. The objective is to understand the teacher training of those who work in rural education and what are the advances and impasses in this process through research in the area. In this study, it is necessary to pay attention not only to the specificity of the school in question not only being a rural school, but also a school that is far from the urban environment and that this in itself characterizes a huge difference when it comes to building teaching-learning relationships. The methodology used for the development of this work was through a literature review, with searches in online journals and magazines, bringing authors who address the theme in question. DOI:https://doi.org/10.56238/sevened2024.009-020